Pengetahuan dan Sikap Pasangan Suami Isteri Mengenai Masalah Kesehatan Reproduksi Perempuan Hubungannya Dengan Partisipasi Pria Dalam Keluarga Berencana - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Problem of gender equality and men responsibility in relationship with reproduction problem and Family Planning is a new paradigm of Family Planning program that established from Kairo Agreement in 1994. One of the obstacles in improving men participation in Family Planning is community's incorrect attitude that tends to consider women as the target of reproduction problem. Incorrect attitude occured as the result of lack of family knowledge regarding problem of women reproduction health. This research was aimed to know the description of sociodemography characteristic, knowledge and attitude of husband and wife regarding problem of women reproduction health. Also, this research was aimed to investigate the relationship between sociodemography characteristic, knowledge and attitude of husband and wife regarding women reproduction health problem with men participation in Family Planning. This was non experimental research with cross sectional design was done in Brebes regency The subjects were couples who had, minimum, 1 child, and still using contraception. The sample was taken with simple random method. Chi Square and logistic regression were used for data analysis. The result of this research showed that sociodemography (income and place of service), knowledge of family regarding women reproduction health problem, and attitude of family regarding women reproduction health problem, were faktors that had relationship with men participation in Family Planning (p0,05).